Elevated Adiponectin Serum Levels in Women with Systemic Autoimmune Diseases - Éric Toussirot; Béatrice Gaugler; Malika Bouhaddi; Nhu Uyen Nguyen; Philippe Saas; Gilles Dumoulin (Mediators of Inflammation)
Adipose tissue produces a wide range of proteins that may influence the immune system. In this study, we assessed the serum levels of leptin, adiponectin, and ghrelin, in association with the measurements of body composition, in 15 female patients with various autoimmune diseases (systemic lupus erythematosus, primary Sjögren's syndrome, sarcoidosis, mixed connective tissue disease, vasculitis, CREST syndrome, and polymyositis) and in 15 healthy female controls. There were no statistically significant differences between the patients and controls with regard to serum leptin, serum ghrelin, global fat mass, adiposity, and fat mass in the android or gynoid regions, whereas serum adiponectin levels were higher in patients than controls (16.3±1.6 μg/mL versus 9.7±0.6 μg/mL; 𝑃=.01). As adiponectin is known to exhibit potent anti-inflammatory properties, a high adiponectinemia in patients with systemic autoimmune disease may mitigate the inflammatory response. However, the precise consequences of these elevated serum adiponectin levels on the metabolic syndrome development and atherosclerotic cardiovascular risk in this patient population still needs to be determined.